Phenotypic changes caused by melatonin increased sensitivity of prostate cancer cells to cytokine‐induced apoptosis. Issue 1 (28th June 2012) - Rodriguez‐Garcia, Aida; Mayo, Juan C.; Hevia, David; Quiros‐Gonzalez, Isabel; Navarro, Maria; Sainz, Rosa M.
Abstract : Abstract: Melatonin has antiproliferative properties in prostate cancer cells. Melatonin reduces proliferation without increasing apoptosis, and it promotes cell differentiation into a neuroendocrine phenotype. Because neuroendocrine cells displayed an androgen‐independent growth and high resistance to radiotherapy and chemotherapy, the role of molecules that induce neuroendocrine differentiation was questioned in terms of their usefulness as oncostatic agents. By using human epithelial androgen‐dependent and androgen‐independent prostate cancer cells, the role of melatonin in drug‐induced apoptosis was studied after acute treatments. In addition to cytokines such as hrTNF‐alpha and TRAIL, chemotherapeutic compounds, including doxorubicin, docetaxel, or etoposide, were employed in combination with melatonin to promote cell death. Melatonin promotes cell toxicity caused by cytokines without influencing the actions of chemotherapeutic agents. In addition, antioxidant properties of melatonin were confirmed in prostate cancer cells. However, its ability to increase cell death caused by cytokines was independent of the redox changes. Finally, phenotypic changes caused by chronic treatment with the indole, that is, neuroendocrine differentiation, make cells significantly more sensitive to cytokines and slightly more sensitive to some chemotherapeutic compounds. Thus, melatonin is a good inhibitor of the proliferation of prostate cancer cells, promoting phenotypic changes that do not increase survival mechanisms and make cells more sensitive to cytokines such as TNF‐alpha or TRAIL.